Evaluating specimen pooling for Neisseria gonorrhoeae, Chlamydia trachomatis, and Mycoplasma genitalium screening in asymptomatic men who have sex with men. (July 2022) - Moran, Angelica; Gipson, Monique; Hazra, Aniruddha; Tesic, Vera
Background: Screening for Neisseria gonorrhoeae and Chlamydia trachomatis is recommended for individuals at high-risk for sexually transmitted infections (STIs), while the role of Mycoplasma genitalium screening is still unclear. We evaluated whether specimen pooling is an effective alternative for sexually transmitted infection testing during resource shortages. Methods: This 2-year prospective study enrolled 135 asymptomatic patients from a community outreach site who identified as men who have sex with men. Oropharyngeal, urine, and/or rectal swab specimens were pooled and tested using the Aptima Combo 2 assay for Neisseria gonorrhoeae and Chlamydia trachomatis . The Aptima Mycoplasma genitalium assay was performed on 34 patients whose specimens had sufficient sample volume for additional testing. Results from pooled specimens were compared to results obtained by individual-site testing. Results: The positive percent agreement (PPA) between pooled testing and individual-site testing was 93.8% and negative percent agreement (NPA) was 100% for Neisseria gonorrhoeae . For Chlamydia trachomatis, the PPA was 85.7% and NPA was 99.2%. A PPA of 72.7% and NPA of 95.7% were observed for Mycoplasma genitalium . Discrepancy analysis revealed the majority of false-negative pools were from failure to detect positive rectal samples. Conclusions: Specimen pooling reduces sensitivity of the Aptima assays for Chlamydia trachomatis, Neisseria gonorrhoeae, and Mycoplasma genitalium and thus should be used with caution.